Native nations : a millennium in North America - DuVal, Kathleen (Random House, 2024)
"In this magisterial history of the continent, Kathleen DuVal traces the power of Native nations from the rise of ancient cities more than 1000 years ago to the present. She reframes North American history, noting significantly that Indigenous civilizations did not come to a halt when a few wandering explorers or hungry settlers arrived, even when the strangers came well-armed. A millennium ago, North American cities rivaled urban centers around the world in size, but following a period of climate change and instability DuVal shows how numerous nations emerged from previously centralized civilizations. From this urban past, patterns of egalitarian government structures, complex economies and trade, and diplomacy spread across North America. And, when Europeans did arrive in the 16th century, they encountered societies they did not understand and whose power they often underestimated. For centuries, Indigenous people maintained an upper hand and used Europeans in pursuit of their own interests. In Native Nations, we see how Mohawks closely controlled trade with the Dutch--and influenced global trade patterns--and how Quapaws manipulated French colonists. With the American Revolution, power dynamics shifted, but Indigenous people continued to control the majority of the continent. The Shawnee brothers Tecumseh and Tenskwatawa built alliances across the continent and encouraged a controversial new definition of Native identity to attempt to wall off U.S. ambitions. The Cherokees created new institutions to assert their sovereignty to the U.S. and on the global stage, and the Kiowas used their preponderance of power in the west to regulate the passage of white settlers across their territory. The definitions of power and means of exerting it shifted over time, but the sovereignty and influence of Indigenous nations has been a constant"--